Motivation Unlocks Gen Z’s Path to Workforce Success: Motivasi Membuka Jalan Gen Z Menuju Kesuksesan di Dunia Kerja - Maharani, Karula Yuan; Rini, Hesty Prima; Sugito (Universitas Muhammadiyah Sidoarjo, 2024)
This study looks into how learning motivation influences the relationship between self-efficacy, competence, and employment preparedness among Generation Z students. The study focuses on twelfth-grade accounting students at SMK Negeri 2 Buduran Sidoarjo in the academic year 2023/2024. The study intends to investigate how self-efficacy and competence influence job preparedness, as well as how learning motivation acts as a mediator in this relationship. A quantitative approach was used to collect data from a sample of 60 pupils from a population of 108, as calculated by Slovin's formula. A questionnaire was utilized to collect data, and the findings were assessed using Partial Least Squares (PLS) analysis. The findings show that self-efficacy and competence have a favorable and significant impact on students' work preparation, with learning motivation successfully moderating the link. These findings indicate that promoting self-efficacy, competence, and learning motivation in vocational education can improve students' preparedness for the workforce